Impact of trait mindfulness on job satisfaction and turnover intentions: Mediating role of work–family balance and moderating role of work–family conflict - Basharat Raza; Muhammad Ali; Khalida Naseem; Abdul Moeed; Jamil Ahmed; Muhammad Hamid (Cogent Business & Management, 2018)
The organizations are facing a problem to keep their employees satisfied and retain them in this era. This study investigates the influence of mindfulness to increase employee job satisfaction and reduce turnover intentions via mediating effect of work–family balance. This research also examines the moderating effect of work–family conflict between the relationship of mindfulness and work–family balance. The real-life organizational empirical data were collected from 306 nurses working in public and private hospitals of Lahore, Pakistan. Structural equation modeling analysis revealed that all hypotheses were supported. Practical implications, limitations, and future directions are also discussed in this study.
Keywords: 650